Applying WRF-CMAQ models for assessment of sulphur and nitrogen deposition in Bulgaria for the years 2016 and 2017. (16th January 2020) - Syrakov, Dimiter; Prodanova, Maria; Georgieva, Emilia; Hristova, Elena
Wet, dry and total depositions of sulphur (S) and nitrogen (N) in Bulgaria are simulated on an annual and seasonal basis for the years 2016 and 2017 using WRF-CMAQ (9 km grid resolution). The mean annual values for wet depositions are about 1, 300 kg.km –2, the dry depositions are slightly lower for S and significantly lower for N (180 kg.km –2 ). The highest modelled wet depositions are in the western and south-western parts of the country, the highest dry depositions – in the northern and eastern parts. The comparison for the wet depositions at three sites with precipitation chemistry data indicates overestimation. A precipitation bias adjustment applied to the modelled depositions results in decrease of the normalised mean bias by a factor of 3. Comparison to modelled deposition data from literature for this region of the country is also provided.